Nonconforming Finite Element Method for the Transmission Eigenvalue Problem (Advances in Applied Mathematics and Mechanics, 2018)
In this paper, we analyze a nonconforming finite element method for thecomputation of transmission eigenvalues and the corresponding eigenfunctions. Theerror estimates of the eigenvalue and eigenfunction approximation are given, respectively.Finally, some numerical examples are provided to validate the theoretical results.